Endovascular Treatment of Intracranial Aneurysms in Small Peripheral Vessel Segments—Efficacy and Intermediate Follow-Up Results of Flow Diversion With the Silk Vista Baby Low-Profile Flow Diverter - Schüngel, Marie-Sophie; Quäschling, Ulf; Weber, Erik; Struck, Manuel Florian; Maybaum, Jens; Bailis, Nikolaos; Arlt, Felix; Richter, Cindy; Hoffmann, Karl-Titus; Scherlach, Cordula; Schob, Stefan (Frontiers in Neurology, 2021)
Background and Purpose: Low-profile flow diverter stents (FDS) quite recently amended peripheral segments as targets for hemodynamic aneurysm treatment; however, reports on outcomes, especially later than 3 months, are scarce. This study therefore reports our experience with the novel silk vista baby (SVB) FDS and respective outcomes after 8 and 11 months with special respect to specific adverse events. Materials and Methods: Forty-four patients (mean age, 53 years) harboring 47 aneurysms treated with the SVB between June 2018 and December 2019 were included in our study. Clinical, procedural, and angiographic data were collected. Follow-ups were performed on average after 3, 8, and 11 months, respectively. Treatment effect was assessed using the O'Kelly Marotta (OKM) grading system. Results: Overall, angiographic follow-ups were available for 41 patients/45 aneurysms. Occlusion or significant reduction in aneurysmal perfusion (OKM: D1, B1–B3 and A2–A3) was observed in 98% of all aneurysms after 8 months. Only 2% of the treated aneurysms remained morphologically unaltered and without an apparent change in perfusion (OKM A1). Adverse events in the early post-interventional course occurred in seven patients; out of them, mRS-relevant morbidity at 90 days related to FDS treatment was observable in two patients. One death occurred in the context of severe SAH related to an acutely ruptured dissecting aneurysm of the vertebral artery. Conclusion: The SVB achieves sufficient occlusion rates of intracranial aneurysms originating from peripheral segments, which are comparable to prior established conventional FDS with acceptably low complication rates. However, alteration of a hemodynamic equilibrium in distal localizations requires special attention to prevent ischemic events.